Measuring State Highway Sustainability: Taking the Fiscal Dimension Into Account. (July 2014) - Chen, Can
Sustainability is vital to the future of America's transportation infrastructure. Achieving a sustainable highway system contributes to overall transportation development. This article focuses on the development of a sustainability index that can be used to measure and benchmark state highway transportation systems. The index was derived from a principal components analysis (PCA) of 2007 U.S. state highway systems data. Seventeen variables measuring four dimensions of highway sustainability were utilized to derive a composite index. This study finds a wide variation in highway sustainability across the U.S. states and regions. The PCA-based index provides a simple and robust measure of state highway sustainability, enables benchmarking and tracking state highway performance, and helps states identify viable strategies for addressing the challenges toward a sustainable highway transportation system.